2013
DOI: 10.1007/s12083-013-0203-9
|View full text |Cite
|
Sign up to set email alerts
|

P2P storage systems: Study of different placement policies

Abstract: In a P2P storage system using erasure codes, a data block is encoded in many redundancy fragments. These fragments are then sent to distinct peers of the network. In this work, we study the impact of different placement policies of these fragments on the performance of storage systems. Several practical factors (easier control, software reuse, latency) tend to favor data placement strategies that preserve some degree of locality. We compare three policies: two of them are local, in which the data are stored in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Irrespective of the overlay upon which the storage technique has been designed on, the most important consideration is guarantee on data availability. In most distributed systems, this is achieved through the inclusion of data redundancy mechanisms which utilize replication and/ or erasure codes [128]. We discuss how this is achieved.…”
Section: Storage Techniques and Redundancymentioning
confidence: 99%
See 2 more Smart Citations
“…Irrespective of the overlay upon which the storage technique has been designed on, the most important consideration is guarantee on data availability. In most distributed systems, this is achieved through the inclusion of data redundancy mechanisms which utilize replication and/ or erasure codes [128]. We discuss how this is achieved.…”
Section: Storage Techniques and Redundancymentioning
confidence: 99%
“…In addition to selecting an appropriate coding technique, another challenge is maintaining a minimum number of data fragments in the network for durable long-term storage in spite of failures by ensuring proper fragment placement. It has been shown that the choice of fragment placement has an impact on system performance [128]. Therefore, not only is the coding technique important, but also the replica placement policy.…”
Section: Data Availability Through Erasure Codingmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we propose a novel RegTech[1] approach for financial transaction as well as financial risk reporting, which is based on cutting-edge distributed computing and decentralised data management technologies such as distributed ledger (DL) (Swanson, 2015), distributed storage[2] (Chandra et al, 2013;Caron et al, 2014), algorithmic financial contract standards (Brammertz and Mendelowitz, 2014;Breymann and Mendelowitz, 2015;Braswell, 2016), automated legal text [3] (Hazard and Haapio, 2017) and document engineering methods and techniques [4] (Glushko and McGrath, 2005). Our approach also takes inspiration from the concept of the "bearer service" and its capacity to span over existing and future technological systems and substrates (Kavassalis et al, 2000, Clark, 1988 [5].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more and more works focused on the replica placement in data grids (Benoit et al, 2008;Grace and and Manimegalai, 2014;Hamrouni et al, 2015b). This problem was considered as a complex optimisation problem (Challal and Tebibel, 2010), and several strategies and heuristics are proposed in the literature in order to solve it (Caron et al, 2007;Rasool et al, 2007). Indeed, there is no polynomial time algorithm for the problem that yields to an optimal solution, i.e., an optimal placement of replicas will always lead to exponential time algorithms (Thara et al, 2013).…”
Section: Introduction and Motivationsmentioning
confidence: 99%